Analisis Kinerja Terminal Leuwipanjang Terhadap Pergerakan Kota Bandung - Angestiwi, Tiafahmi; Rakhmatulloh, Anita Ratnasari (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Leuwipanjang Terminal acts as a transportation node connecting Bandung City and centers of activity around it through bus service in the city, inter city and inter province routes. This study examines the performance of Leuwipanjang Terminal in its role in supporting movements between centers of activities in Bandung City using positivistic-quantitative approach through descriptive analysis. Primary data is collected through field observation surveys, questionnaires and interviews with the head of the UPTD (the terminal operator), angkot drivers, and Damri bus conductors. Samples of angkot and Damri passengers are determined through accidental sampling to 100 people while samples of drivers and conductors are determined through purposive sampling. Secondary data is acquired from the Transportation Office and Terminal UPTD. Analysis showed that Leuwipanjang Terminal’s performance is fairly good. The interaction between Leuwipanjang Terminal and centers of activities in Bandung City constructs a dynamic power in the form of centripetal and centrifugal force. The city core center and Ir. H. Juanda Area gave a dynamic centripetal force from the fringes to the city centers, while Surya Sumantri industrial and educational area created a centrifugal force from the city centers to the fringes.